The Process of Technological Innovation Reviewing the Literature. - National Science Foundation, Washington, DC.; National Science Foundation, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
This review of literature concerned with technological innovation and innovation process research is divided into five general parts. Part I defines basic concepts and terms and outlines major analytical themes. Part II develops the individual and organizational dimensions within which innovative activities take place. In Part III, the sequence of events from technology generation to implementation and dissemination is described, and strategic options available to organizations in the management of innovation are discussed. An assessment of the role of government in affecting organizational technology is provided in Part IV and Part V presents a list of conclusions drawn from the review. These conclusions focus on the stages of innovation, the social units involved in the innovation process, perceptions of innovation by technology producers and users, indices of innovation, uncertainty about new technologies, the relationship between innovation and organizational size and structure, innovation in public and private sector organizations, characteristics of innovative individuals, the relationship of the research and development (R&D) function to innovation, the implementation of innovation, technology transfer, university/industry research interactions, the innovativeness of small high-technology based firms, and the effects of regulation and other government policies on innovation. An extensive list of references concludes the publication. (ESR)
Researchers.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Government Role; Individual Activities; Industry; Literature Reviews; Organizational Climate; Organizations (Groups); Research and Development Centers; Research Utilization; School Business Relationship; Technological Advancement; Technology Transfer; Innovators -- Technological Change; Information Analyses